Boys and girls in no man's land : English-Canadian children and the First World War - Fisher, Susan, 1948- (University of Toronto Press, 2011)
Drawing on educational materials, textbooks, adventure tales, plays, and Sunday-school papers, Boys and Girls in No Man's Land explores the role of children in the nation's war effort.